ANALISIS HARGA DAN DISTRIBUSI PEMASARAN IKAN KEMBUNG (Rastrelliger sp) DI PELABUHAN PERIKANAN PANTAI TAWANG KABUPATEN KENDAL JAWA TENGAH - Hanggaretna, Justinus Bella; Triarso, Imam (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Catch that was landed on Beach Fisheries Port Tawang (PPP Tawang) on 2011 reached 106,200 kg. The aims this research were to know fluctuations of mackerel the price the daily and monthly, to know and analyze of price level determination mackerel fish (y) with each variable price setter mackerel fish was production quantities mackerel fishfish (x1), the number of seller auction participants (x2), fish size (x3) ,fish quality (x4), number of substitute fish production (x5), fish production substitutes rates (x6), and to know mackarel distribution near Beach Fisheries Port Tawang (PPP Tawang), Kendal Residence, Central Java Province. Research method used quantitative descriptive by observation techniques using fishermen, seller, and fish processor interview. Data analyzis used Cobb-Douglass method, with the equation Ln Y = 5.929 – 0,044 X1 + 0,249 X2 + 0,317 X3 + 0,100 X4 + 0,036 X5 + 0,087 X6 . Regression analyzing variable X1, X2, X3, X4, X5 and X6 to F hit results variable was 5.580 which is the value was bigger than F table on interval 5% was 2,510. It means x1, x2, x3, x4, x5 and x6 had real influence to mackerel fish price in Beach Fisheries Port Tawang ( PPP Tawang). Mackerel distribution line from producer by Beach Fisheries Port Tawang (PPP Tawang) to consumer was short enough because it involved by few people. They are grocier seller, fish processor, big seller, and small seller. The destination were Kendal area until Semarang, Cirebon, Cianjur, Jakarta, and Lampung.